Ameliorative potential of fluoxetine/raloxifene combination on experimentally induced breast cancer. Issue 2 (April 2016) - Kabel, Ahmed M.; Elkhoely, Abeer A.
Highlights: Raloxifene/fluoxetine combination had a better effect than the use of each of these drugs alone against DMBA-induced breast cancer. This might represent a new therapeutic modality for management of breast cancer. Abstract: Breast cancer is one of the most common types of malignancies in females worldwide. Targeting the estrogen receptors alone with raloxifene (RAL) reduces the incidence of estrogen receptor positive tumors. Fluoxetine (FLX) is one of selective serotonin reuptake inhibitors that was proven to have anticancer properties. Our aim was to detect the effects of RAL/FLX combination on experimentally induced breast cancer. Eighty female Wistar rats were divided into four equal groups: 7, 12-Dimethyl Benzanthracene (DMBA) induced breast cancer group, DMBA + RAL, DMBA + FLX and DMBA + RAL + FLX. Tumor volume, tissue malondialdehyde (MDA), catalase (CAT), superoxide dismutase (SOD), tumor necrosis factor-alpha (TNF-α), interleukin 6 (IL-6) and transforming growth factor beta1 (TGF-β1) were determined in the tumor tissues. Parts of the tumor were subjected to histopathological examination. RAL or FLX alone or in combination induced significant increase in tumor CAT and SOD with significant decrease in tumor volume, tissue MDA, TNF-α, IL-6 and TGF-β1 and alleviated the histopathological and immunohistochemical changes compared to DMBA group. In conclusion, RAL/FLX combination had a better effect than each of RAL or FLX alone against DMBA-induced breast cancer in rats which may represent a new therapeutic modality for management of breast cancer.